Use of OCL in a Model Assessment Framework: An experience report - Chimiak-Opoka, Joanna; Lenz, Chris (Electronic Communications of the EASST, 2007)
In a model assessment framework different quality aspects can be examined. In our approach we consider consistency and perceived semantic quality. The former can be supported by constraints and the later by queries. Consistency can be checked automatically, while for the semantic quality the human judgement is necessary. For constraint and query definitions the utilisation of a query language was necessary. We present a case study that evaluates the expressiveness of the Object Constraint Language (OCL) in the context of our approach. We focus on typical queries required by our methodology and we showed how they can be formulated in OCL. To take full advantage of the languageâs expressiveness, we utilise new features of OCL 2.0. Based on our examination we decided to use OCL in our analysis tool and we designed an architecture based on Eclipse Modeling Framework Technology.